Application of Transthoracic Echocardiography for Cardiac Safety Evaluation in the Clinical Development Process of Vaccines Against Streptococcus pyogenes - Usman Nakakana; Alimamy Serry-Bangura; Bassey Effiom Edem; Pietro Tessitore; Leonardo Di Cesare; Danilo Gomes Moriel; Audino Podda; Iris Sarah De Ryck; Ashwani Kumar Arora (Adis, Springer Healthcare, 2024)
Abstract Superficial infections with Streptococcus pyogenes (Strep A), pharyngitis and impetigo can induce acute rheumatic fever, an autoimmune sequela manifesting mostly with arthritis and rheumatic carditis. Valvular heart damage can persist or advance following repeated episodes of acute rheumatic fever, causing rheumatic heart disease. Acute rheumatic fever and rheumatic heart disease disproportionately affect children and young adults in developing countries and disadvantaged communities in developed countries. People living with rheumatic heart disease are at risk of experiencing potentially fatal complications such as heart failure, bacterial endocarditis or stroke. Transthoracic echocardiography plays a central role in diagnosing both rheumatic carditis and rheumatic heart disease. Despite the obvious medical need, no licensed Strep A vaccines are currently available, as their clinical development process faces several challenges, including concerns for cardiac safety. However, the development of Strep A vaccines has been recently relaunched by many vaccine developers. In this context, a reliable and consistent safety evaluation of Strep A vaccine candidates, including the use of transthoracic echocardiography for detecting cardiac adverse events, could greatly contribute to developing a safe and efficacious product in the near future. Here, we propose a framework for the consistent use of transthoracic echocardiography to proactively detect cardiac safety events in clinical trials of Strep A vaccine candidates.